Publisher Correction: Unravelling the structure of glycosyl cations via cold-ion infrared spectroscopy. Issue 1 (December 2018) - Mucha, Eike; Marianski, Mateusz; Xu, Fei-Fei; Thomas, Daniel; Meijer, Gerard; Helden, Gert; Seeberger, Peter; Pagel, Kevin
The original version of this Article contained an error in Fig. 1, in which an oxygen atom was missing from the 'Acetoxonium type' structure. This has been corrected in both the PDF and HTML versions of the Article.